Involvement of matrix metalloproteinase activity in hormone-induced mammary tumor regression - Simian, Marina (2006)
Proteolytic activity and remodeling of the extracellular matrix are important players in tumor progression. However, to date the role of the extracellular matrix in tumor regression remains unresolved. To address this, we used a progesterone-dependent in vivo mouse mammary tumor line, C4-HD, which regresses in response to hormone therapy. Within the first 72 hours of treatment, massive apoptosis was accompanied by changes in the staining patterns of laminin and collagens I, III, and IV. We thus hypothesized that an increase in matrix metalloproteinase (MMP) activity could be involved in this process. This indeed was the case as the activities of MMP-2, -9, and -3 increased in regressing tumors, coinciding with the peak of apoptosis. Moreover, cell-cell interactions were disrupted during early hours of regression with E-cadherin levels reduced and fragmentation products detected during regression. Analysis of β-catenin revealed that although total levels within the tissue did not change, this molecule switched from being involved in cell-cell adhesion in the growing tumor to being expressed in the reactive stroma during regression. Our data provide a novel role for proteolytic activity in tumor regression and question the underlying principle for using MMP inhibitors in cancer treatment.